Patterns of neck metastasis and occult neck disease during recurrent laryngeal cancer. Issue 5 (25th May 2023) - Rovira, A; Brunet, A; Tornari, C; Ofo, E; Jeannon, J-P; Williamson, P; Oakley, R; Kim, D; Arora, A; Oikonomou, G; Odutoye, T; Simo, R
Abstract: Objective: Numerous factors are considered to impact on the rate of complications during salvage total laryngectomy procedures. Neck dissection could be one of these factors. This study analysed the pattern of lymph node metastasis and rate of occult neck disease during salvage total laryngectomy as well as the impact of neck dissection on survival and complication rates. Method: This was a retrospective analysis of a prospectively maintained laryngectomy database in two large tertiary teaching hospitals. Results: The rate of occult neck disease was 11.1 per cent. Most cases with occult neck disease had rT4 disease. Patients with complications, advanced tumour stage and positive margins had a significant decrease in overall survival. Patients receiving elective neck dissection did not have any survival benefit. Positron emission tomography-computed tomography showed a very high specificity and negative predictive value. Conclusion: According to the low risk of occult neck disease when using contemporary imaging techniques as well as the lack of impact on survival, conservative management of the neck should be considered for crT1 -T3 recurrence.